Efeitos da adição e da bioestimulação da produção de biossurfactantes in situ, durante a biorremediação de solo argiloso contaminado com óleo diesel-B10 - Decesaro, Andressa (2021)
Diesel oil is one of the most widely used fuels worldwide. Diesel oil leaks in underground storage tanks during transport and distribution represent an important source of soil and aquifer contamination. The treatment of soil contaminated with diesel can be carried out by means of physical, chemical and also biological methods. Bioremediation is considered promising, as it is a biological technique that can be applied to large contaminated areas. In addition, research on the influence of biosurfactants on the efficiency of contaminated soil bioremediation is growing steadily. However, despite constant advances in understanding the mechanisms involved in the effects of biosurfactants, there are still many factors that are not sufficiently elucidated. There is a lack of research on autochthonous or exogenous microbial metabolism when biostimulation or bio-enhancement is performed to produce biosurfactants in contaminated sites. Thus, this study had as its general objective, the evaluation of the production of biosurfactant in the soil and to verify the influence of biocomposites on the process of retention and biodegradation of the contaminant. Initially, surfactin was produced through submerged fermentation using the bacteria Bacillus methylotrophicus and whey as a culture medium, to develop methodologies for measuring biosurfactants in aqueous medium. The biosurfactant produced was added to the soil and studies were carried out to develop a methodology for extracting the biocomposite from the soil and its measurement. In a second step, we investigated the retention of diesel oil-B10 (B10: 90% diesel; 10% biodiesel) in clayey soil during biostimulation by bacterial biosurfactants (surfactin or ramnolipid). In the third phase of the study, bioremediation was carried out on soil contaminated with 20% diesel-B10 oil, using bio-stimulation and bio-augmentation strategies to stimulate the production of biosurfactants in the soil. Biosurfactants were produced in the amount of interest, used for the elaboration of standard curves by surface tension and Biuret method. Regarding the effect of adding biosurfactants (surfactin and ramnolipid) on the soil on retention, it was found that it was not a significant factor in the concentrations used, and did not interfere with the adsorption of the contaminant. Thus, it can be said that the insertion of biosurfactants in sufficient quantity for an effective bioremediation does not affect the percolation of the contaminant in the soil. In the bioremediation test with diesel oil, the treatment with the application of biostimulation and bioincrease together showed 61.66% of total removal at the end of 120 days of the experiment. The production of biosurfactants in the soil, evaluated by measuring the surface tension of the soil extracts, showed a reduction in the surface tension for the bio-enhancement and biostimulation treatments (11.82%), indicating the release of biosurfactants in the medium. This trend was not observed in natural attenuation and control treatments. For sterile soil, the values referring to adsorption were around 20%, not differing statistically from each other, demonstrating that the different biostimulants did not promote different rates of adsorption of the contaminant, corroborating with the previous study. Thus, it was found that the joint application of biostimulation and bioincrease techniques helped in the production of biosurfactants directly in the soil and increased the biodegradation of diesel oil in the soil.